No One to Bear Witness: Country Information and LGBTQ Asylum Seekers - McDonald-Norman, Douglas (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2017)
This article examines the use of country information in determining claims for refugee status based on sexual orientation or gender identity. Limitations to country information remove diverse individual experiences from the “historical record” and obstruct marginalized individuals’ ability to prove their claims for protection. Discrimination and marginalization may be echoed and perpetuated within country information itself, which privileges certain voices over others. MD (same-sex-oriented males: risk) India CG [2014], the United Kingdom’s current “country guidance” decision on claims for protection by same-sex oriented men from India, is examined in light of these themes.